Invoking Cultural Awareness Through Teaching Indigenous Issues in Criminal Law and Procedure - Thalia Anthony; Melanie Schwartz (Legal Education Review)
This paper offers a typology for rethinking the case for mandatory legal ethics education in the English law degree, by considering legal ethics education in other common law jurisdictions alongside the fundamental role which is played by legal culture, values and ethics in international commercial arbitration. Traditional undergraduate and post-graduate legal ethics education is often focused on the law of lawyering: the professional regulation of lawyer conduct, legal practice and legal services. However the field of international arbitration (IA), which is increasingly dominated by lawyers, helps to illustrate why legal ethics has arguably become a substantive body of legal knowledge in its own right. It deserves separate critical study due to increasing demands for a heightened sensitivity to cross-cultural values in all law graduates who are moving into transnational legal and non-legal professional environments, within and beyond the field of IA. A new paradigm for legal ethics education may thus be relevant for all jurisdictions.